Management of cardiac tamponade during nivolumab of lung cancer with intrapericardial bleomycin: case report. (7th February 2019) - Asai, Maiko; Kato, Yasuhiro; Kawai, Shoko; Watanabe, Kageaki; Yomota, Makiko; Okuma, Yusuke; Hosomi, Yukio; Hishima, Tsunekazu; Okamura, Tatsuru
Immuno-checkpoint inhibitor response and immune-related adverse events remain controversial issues. Managing pericardial effusion during programmed cell death 1 inhibitor treatment is challenging. Here, we report a case of successfully managed cardiac tamponade caused by nivolumab-induced pseudoprogression. A 62-year-old male diagnosed with advanced lung adenocarcinoma started on nivolumab. Seven days later, he experienced cardiac tamponade and required pericardiocentesis, and other lesions were larger on computed tomography. The patient's condition stabilized after pericardiocentesis. However, although the lesions other than pericardial effusion were reduced on chest CT, cardiac tamponade recurred after 6 weeks. We considered that the case involved cardiac tamponade induced by pseudoprogression and administered intrapericardial bleomycin after pericardiocentesis. Thereafter, the patient was administered nivolumab for 7 months until disease progression.